Jamaica : Fifth Review Under the Extended Fund Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2014)
EXECUTIVE SUMMARY Recent data show a gradual economic recovery, with growth projected to reach just over 1 percent in 2014/15. Inflation has trended down to about 8 percent. The program is on track. Jamaica's four-year, SDR 615.38 million (225 percent of quota) Extended Arrangement under the EFF was approved by the IMF Executive Board on May 1, 2013, and the first four reviews under the program were completed on schedule. All end- June 2014 quantitative performance criteria were met. The structural benchmarks for end- June were also met. Based on the strong performance to date and the authorities' updated policy intentions and commitments, staff recommends completion of the fifth review under the extended arrangement. Focus of the review. Discussions centered on the preparations for the 2015/16 budget and financial sector reforms. The program has been updated, with steps to support the ambitious fiscal goals by strengthening tax administration, enhancing public financial management, and containing the civil service wage bill. Further steps have been articulated to move ahead the reform of the securities dealers sector and to strengthen the financial system more broadly. Progress in implementing the authorities' program is steadily advancing with every successful review, but risks to the program remain relatively high. A delayed growth recovery could undermine social support for the reform efforts, financial sector vulnerabilities could become more pressing, or risks to external financing (including from PetroCaribe) could crystallize. A further challenge will be to keep the budget on track in the face of risks to revenues and the wage bill.